Objectification decreases prosociality: the mediating role of relative deprivation - Zhang, Zaixuan; Chen, Zhansheng; Poon, Kai-Tak; Jiang, Tonglin (Frontiers in Psychology, 2023)
Objectification denies individuals’ personhood and renders them as tools for facilitating others’ goal achievement. With two studies (N = 446), the present investigation aimed to contribute to the literature by testing whether and how objectification impacts prosociality, including prosocial intention and prosocial behavior. Study 1, with a correlational design, aimed to test whether participants with greater experience of objectification would report lower levels of prosociality, and to test whether participants’ perceived relative deprivation could account for the proposed association between objectification and prosociality. To further test these associations and provide causal evidence, in Study 2, we manipulated objectification by asking participants to imagine future objectification experiences. These studies converged in support of the causal effect of objectification on prosocial intention as well as on the mediating role of relative deprivation. Regarding prosocial behavior, our findings support a mediating mechanism between objectification and prosocial behavior, although the evidence for the effect of objectification on prosocial behavior is not sufficient. These findings enrich our understanding of the consequences of objectification, while highlighting interpersonal processes’ contribution to prosocial intention and behavior. The limitations and potential future directions are also discussed.